2021
DOI: 10.5114/ait.2021.103526
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of bioelectrical impedance analysis for assessment of fluid overload in ICU patients: a pilot study

Abstract: Background The non-invasive analysis of body fluid composition with bio-electrical impedance analysis (BIA) provides additional information allowing for more persona-lised therapy to improve outcomes. The aim of this study is to assess the prognostic value of fluid overload (FO) in the first week of intensive care unit (ICU) stay. Methods A retrospective, observational analysis of 101 ICU patients. Whole-body BIA measurements were performed, and FO was defined as a 5% i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…Use of a protocol including blood volume analysis with calculation of total circulating blood volume by albumin-marked isotope dilution technique resulted in a 66% reduction in mortality, 20% reduction in length of stay (LOS), 36 h earlier treatment decisions and change of treatment strategy in 44% (reduced fluid and diuretic administration in 50% of cases) [ 11 ]. A 5% increase in volume excess from baseline, measured by bio-electrical impedance analysis, was associated with increased mortality in a retrospective study of 101 critically ill patients [ 12 ]. Another study in 125 patients showed that the hydration status measured by bio-electrical impedance vector analysis (BIVA) seems to predict mortality risk in intensive care unit (ICU) patients better than the conventional method of fluid balance recording [ 13 ].…”
Section: When To Start Deresuscitation?mentioning
confidence: 99%
“…Use of a protocol including blood volume analysis with calculation of total circulating blood volume by albumin-marked isotope dilution technique resulted in a 66% reduction in mortality, 20% reduction in length of stay (LOS), 36 h earlier treatment decisions and change of treatment strategy in 44% (reduced fluid and diuretic administration in 50% of cases) [ 11 ]. A 5% increase in volume excess from baseline, measured by bio-electrical impedance analysis, was associated with increased mortality in a retrospective study of 101 critically ill patients [ 12 ]. Another study in 125 patients showed that the hydration status measured by bio-electrical impedance vector analysis (BIVA) seems to predict mortality risk in intensive care unit (ICU) patients better than the conventional method of fluid balance recording [ 13 ].…”
Section: When To Start Deresuscitation?mentioning
confidence: 99%
“…Third, we did not obtain data regarding fluid balance since our principal objective was to confirm that EVLW measured by TPTD is associated with a worse outcome. Fourth, we did not investigate EVLW as an adjunctive variable to other techniques, such as ultrasonography and bioelectrical impedance, to evaluate the fluid status [ 54 ]. Finally, we limited our search to articles published in English language and did not expand our search to clinical trial registry databases.…”
Section: Discussionmentioning
confidence: 99%
“…ICU and surgical patients often require advanced hemodynamic monitoring, which should be accurate and reliable. For some assessments, such as the patient’s fluid status, less invasive methods can be helpful [ 11 ]. However, other patients require more invasive monitoring, for which more precise and invasive tools are necessary.…”
Section: Discussionmentioning
confidence: 99%